2013
DOI: 10.1101/gr.162933.113
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial, epithelial, and fibroblast cells exhibit specific splicing programs independently of their tissue of origin

Abstract: Alternative splicing is the main mechanism of increasing the proteome diversity coded by a limited number of genes. It is well established that different tissues or organs express different splicing variants. However, organs are composed of common major cell types, including fibroblasts, epithelial, and endothelial cells. By analyzing large-scale data sets generated by The ENCODE Project Consortium and after extensive RT-PCR validation, we demonstrate that each of the three major cell types expresses a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 50 publications
(114 reference statements)
2
68
0
Order By: Relevance
“…1B; Mallinjoud et al 2014). In so doing, FasterDB genomic exons were associated with one or several EXONT terms and a web interface was developed in order to easily retrieve the EXONT terms associated with genomic exons (Fig.…”
Section: Exon Ontology Tree and Exon Annotationmentioning
confidence: 99%
See 2 more Smart Citations
“…1B; Mallinjoud et al 2014). In so doing, FasterDB genomic exons were associated with one or several EXONT terms and a web interface was developed in order to easily retrieve the EXONT terms associated with genomic exons (Fig.…”
Section: Exon Ontology Tree and Exon Annotationmentioning
confidence: 99%
“…For example, the selective expression of protein isoforms plays a major role in the biological functions of epithelial and mesenchymal cells, which are two major cell types found in many tissues (Bebee et al 2014;Mallinjoud et al 2014;Yang et al 2016b). Epithelial and mesenchymal cells ensure different physiological functions (epithelial cells are interconnected and nonmotile cells, while mesenchymal cells are isolated and motile cells), and the epithelial-to-mesenchymal transition has been shown to contribute to metastasis formation during tumor progression (Bebee et al 2014;Yang et al 2016b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exon-array data were analysed with Expression Console (Affymetrix) to perform quality assessment and normalized using quintile normalization. Background correction and probe selection were performed as previously described, using exon annotation from the Faster DB database 22,60 (http://fasterdb.lyon.unicancer.fr/). Global gene regulation was calculated based on exonic probes from the whole gene.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study revealed that NOVA1 is enriched in normal fibroblasts, suggesting involvement in the splicing programs of normal fibroblasts [10]. We previously noted that NOVA1 is expressed in only a small number of T cells within normal physiologic secondary lymphoid structures such as the palatine tonsils [11] .…”
Section: Introductionmentioning
confidence: 99%